Political sociologies of the cultural encounter essays on borders, cosmopolitanism, and globalisation - Axford, Barrie; Brisbourne, Alistair; Halperin, Sandra 1950-; Lueders, Claudia (Routledge, Taylor & Francis Group, 2021)
"This book offers transdisciplinary scholarship which challenges the agendas of and markers around traditional social scientific fields. It builds on the belief that the study of major issues in the global cultural and political economies benefit from a perspective that rejects the limitations imposed by established boundaries, whether disciplinary, conceptual, symbolic or material. Established and early career academics explore and embrace contemporary political sociology following the 'global' and 'cultural' turns of recent decades. Categories such as state, civil society, family, migration, citizenship and identity are interrogated and sometimes found to be ill-suited to the task of analyzing global complexities. The limits of global theory, the challenges of global citizenship, and the relationship between globalization and situated and mobile subjects and objects are all referenced in this book. The book will be of interest to scholars of International Relations, Political Science, Sociology, Political Sociology, Social Theory, Geography, Area studies and European studies."
"Festschrift for professor Chris Rumford"
Keywords: Diffusionismus; Weltbürgertum; Kulturkontakt; Weltgesellschaft; Globalisierung; Politische Soziologie; Political sociology; Civil society; World citizenship; Cosmopolitanism; Culture diffusion; Globalization / Social aspects; POLITICAL SCIENCE / General; POLITICAL SCIENCE / Globalization; POLITICAL SCIENCE / Political Ideologies / General; Festschrift